2011
DOI: 10.3148/72.4.2011.162
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Screening for Seniors in Health Care Facilities: A Survey of Health Professionals

Abstract: These findings will help professionals address the feasibility of implementing standardized screening tools in health care facilities. A more consistent and systematic approach for detecting populations at high nutritional risk may result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 21 publications
0
31
0
1
Order By: Relevance
“…In addition, prevalence alone would suggest that BMI on its own is not sensitive enough, as only 9% of admitted patients were in the underweight BMI category, well below reported malnutrition prevalence rates 1 . ‐ 8 These findings suggest that an anthropometric snapshot in time like BMI is not adequate to assess the nutrition status of patients at hospital admission. In addition, although some 21 reported that higher BMI may be protective, there is a false perception that these patients are in a better nutrition state and have better outcomes; in fact, they may be disadvantaged as they may develop sarcopenia that could be difficult to detect unless a more comprehensive assessment such as SGA is completed.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, prevalence alone would suggest that BMI on its own is not sensitive enough, as only 9% of admitted patients were in the underweight BMI category, well below reported malnutrition prevalence rates 1 . ‐ 8 These findings suggest that an anthropometric snapshot in time like BMI is not adequate to assess the nutrition status of patients at hospital admission. In addition, although some 21 reported that higher BMI may be protective, there is a false perception that these patients are in a better nutrition state and have better outcomes; in fact, they may be disadvantaged as they may develop sarcopenia that could be difficult to detect unless a more comprehensive assessment such as SGA is completed.…”
Section: Discussionmentioning
confidence: 89%
“…The prevalence of hospital malnutrition is between 15% and 70%, 1 8 and the prevalence of obesity is about 30%, 9 , 10 depending on populations, types of institutions, and methods of assessment. For hospital malnutrition, contributors may relate to underlying illnesses, aging, socioeconomic situations, 11 , 12 surgical procedures, lack of nutrition monitoring, and intervention 8 , 13 . For malnutrition detected at admission, preadmission contributors are not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…The full texts of the remaining 31 publications were examined. Eleven met the criteria and were included in the review (Lennard‐Jones et al ., ; Kondrup et al ., ; Savage & Scott, ; Lindorff‐Larsen et al ., ; Hodge, ; Persenius et al ., ; Raja et al ., ; Holst et al ., ; NPSA, ; Porter et al ., ; Villalon et al ., ). Table summarises the methods and findings of the 11 publications.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the five hospital sites were routinely screening, with only two having relatively good completion rates (76 and 66% of patients) and using validated tools. Many barriers to screening have been identified in the literature, including lack of time, low priority among staff, uncertainty in using existing tools, and not having a simple screening tool embedded into routine practice [38,40]. The third site (Site C), with a low coverage of screening at 26% of patients, required a long, cumbersome nutrition screening form, which likely affected their success rate with this care activity.…”
Section: Discussionmentioning
confidence: 99%